Variety of concepts on the prevention of periodontal disease - Falcon-Guerrero, Britto Ebert (2023)
The review of gingivitis and periodontitis, if not properly prevented, can lead to the loss of teeth. In order to have the necessary guideline is that a review is made from the etiology to the means such as probiotics and vaccines, which could make clearer the prevalence of periodontal diseases. In this study, a documentary analysis was carried out based on a search on the subject in bibliographic references of the last 6 years, in the Medline and PubMed databases. Review and research articles related to the topic through the title were evaluated. Thosetopics that did not comply with the database were excluded. The purpose is to review a variety of concepts on the prevention of periodontal disease to allow a clearer understanding of what prevents the implementation of periodontal disease, for the patient and public health.